Pengaruh Metode Amtsilati Dalam Meningkatkan Kemampuan Baca Kitab Kuning Siswa - M. Miftakhul Miftakhul Huda (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
One of the causes of students being slow to be able to read the yellow book is because students are less actively involved, they only listen to what is explained by the teacher and the learning method is less enjoyable. Therefore, there is a need for a more effective and efficient new method to improve students' yellow reading ability. One solution to be able to improve students' yellow reading ability is to apply the Amtsilati method. The purpose of this study was first, to determine the results of the application of the Amtsilatiat the matholiul anwar Middle School in the Maibit Rengel in improving the students' yellow reading ability. Second, to find out whether there is an influence on the application of Amtsilatimethod to the yellow book reading ability at matholiul anwar Middle School, Maibit Rengel. The results were obtained first, there was a significant increase in results between the application of the Amtsilati method in improving the yellow book reading ability of students at Matholiul Anwar Middle School, Maibit Rengel, this was based on hypothesis testing using the T test with a significance value (0,000) < 0.05. Second, there is a significant effect of the application of the Amtsilati method in improving the yellow book reading ability of students at Matholiul Anwar Middle School, Maibit Rengel. This is based on observational data conducted by researchers. The influence is that students understand the learning material faster, students are able to determine the position of reading and students are able to interpret and explain the purpose of reading.